Effect of AKT3 expression on MYC‐ and caspase‐8‐dependent apoptosis caused by polo‐like kinase inhibitors in HCT 116 cells. Issue 12 (19th December 2016) - Nonomiya, Yuma; Noguchi, Kohji; Tanaka, Noritaka; Kasagaki, Takahiro; Katayama, Kazuhiro; Sugimoto, Yoshikazu
Abstract : Polo‐like kinase (PLK) is a cell‐cycle regulator that is overexpressed in several cancer cell types. Polo‐like kinase is considered a novel target for cancer therapies, and several PLK inhibitors (PLKis), including BI 2536, BI 6727, and GSK461364, have been developed. In this study, we established five BI 2536‐resistant cell lines from human colorectal cancer HCT 116 cells, to explore the resistance mechanism and identify predictable biomarkers of PLKis. We showed that PLKi‐induced caspase‐8 activation was attenuated in the BI 2536‐resistant cell lines. We also showed that the expression of P‐glycoprotein (P‐GP) and AKT3 was upregulated, whereas that of MYC was downregulated in some BI 2536‐resistant cell lines. Expression of P‐GP conferred resistance to PLKis, and PLKi‐induced apoptosis was dependent on MYC and caspase‐8 in HCT 116 cells. We also showed for the first time that AKT3 suppressed BI 6727‐induced caspase‐8 activation and conferred resistance to PLKis. Collectively, these results indicate that MYC, caspase‐8, P‐GP, and AKT3 play critical roles in PLKi‐induced apoptosis. Therefore, they are candidate biomarkers of the pharmacological efficacy of PLKis. Abstract : We established PLK inhibitor‐resistant cell lines and demonstrated that MYC, caspase‐8, P‐GP and AKT3 play critical roles in the sensitivity to PLK inhibitors.